(untitled) (Research, Society and Development, 2022)
Introduction: Fibromyalgia Syndrome (FMS), or simply fibromyalgia, is a chronic pain syndrome characterized by generalized pain, tender points, sleep disturbances and extreme fatigue. Objective: to highlight the etiophysiopathogenic hypotheses of fibromyalgia. Methodology: This is a descriptive research of the integrative literature review type. The research was carried out through online access to the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases. Information Services, March 2022. Results and Discussion: Patients with FMS, which is characterized as a pain amplification syndrome, are extremely sensitive to both painful and non-painful stimuli, including touch, heat and cold, and stimuli mechanics. However, it should be noted that the hypersensitivity of these patients is not limited to pain, but also includes light, sound and olfactory stimuli. The cause of this exaggerated sensitivity of FMS patients has not been determined, but several studies have shown abnormalities of pain processing in the CNS. Most of these studies showed central sensitization, indicating a reduction in the nociceptive threshold in the dorsal horn of the spinal cord and in the brain. Although afferent nociceptive stimuli are necessary for the pain of FMS patients, an important feature of sensitization is that very little sustained nociceptive stimulation in peripheral tissues is required for the maintenance of the sensitized state and chronic pain. Final considerations: The etiology of fibromyalgia is still not well understood. Its cause is believed to be essentially multifactorial, with genetic and psychological aspects playing a role in the development of the disease.